Financial support of social protection of the population in countries with developed and transformation economy - Chugunov, Igor Ya.; Nasibova, O. (Akademické sdružení MAGNANIMITAS, Czech Republic, 2021)
The article is devoted to the analysis of functioning models of social protection of the population, which influence the choice of principles of financing social expenditures in countries with developed and transformational economies. The existing typology of social protection systems is studied, their main criteria and features are highlighted. An assessment of the level of financial support for social protection of the population for 2004-2018 is carried out; the total expenditure on social protection per capita in countries with developed and transformational economies are analyzed. Emphasis is made on pension benefits in gross domestic product as the main indicator for assessing the financial capacity of the country's pension system.
Keywords: finance; social benefits; social policy models; social protection; pension expenditures